Introduction - Bieś, Andrzej Paweł (Studia Paedagogica Ignatiana, 2018)
The teaching profession requires constant improvement, learning, as well as work on one’s personal development. The teacher cannot remain in one place and, obviously, one has to admit that Robert Kwaśnica is correct in saying that the teacher must be supported in his or her development, as it is the teacher who influences the students with all his/her being.Since teachers are people burdened with exceptional responsibility—educating young generations, i.e. shaping the future—the task should be fulfilled by the best of the best. As the texts collected in this issue confirm, we can often spot such people. However, the paradox is that practically everyone has access to the job, as “the university education is not a problem for many people, and the personality traits of future teachers are not identified in any way.” What should be done in this situation? How can we change the system of educating teachers? What requirements should be placed before candidates for the job? How can we make sure that educational institutions are provided with teachers whose motto is the Ignatian principle of magis—reaching for more?